Separation of cobalt from spent catalyst CoMo by precipitation and Ion exchange techniques - Al-Taweel, H.H.; Ali, M.J.; Al-Azawi, K.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two methods were established to separate cobalt from the spent catalyst CoMo which also contain Co, Al and Fe. The first method was the precipitation technique by controlling the pH. At pH 5, 76% of the cobalt which was collected with 1.4% Al and 0.5% Fe as contaminants. The second method was the anion exchange by using Amberlite 400 resin, 100% of the cobalt and was collected with 99.46% purity.The only contaminant was Fe with 0.54% with no Al.  For a large scale production of cobalt from this spent catalyst, a batch process was designed with a production of 80 grams per batch by using the anion exchange technique. Kilograms quantities of Co were collected.